Aroma Evaluation of Young Chinese Merlot Wines with Denomination of Origin - Zhang, L.; Tao, Y.S.; Wen, Y.; Wang, H. (South African Journal of Enology and Viticulture, 2016)
Merlot wines from four premium wine-producing districts in China were analysed for their volatile composition and sensory properties. Fifty-seven aroma compounds were quantified by SPME-GC-MSOAV analysis, which showed that thirty of these compounds were active on the basis of their odour active value (OAV). According to the aroma descriptions of eleven impact odorants in all the sample wines, the collective aroma characteristics of Chinese Merlot red wine are complex. Its main flavour is that of some tropical and temperate fruits, such as banana, pineapple, green apple, pear and strawberry, along with a lactic flavour from the malolactic fermentation. It also has some traits of processed fruits, Muscat and floral pollen flavour. Moreover, different districts gave Merlot wine distinct characters. Changli wine had a higher intensity and complexity of global aroma, a strong fruity aroma, and an obvious nuance of lactic and nut traits. The sine from Helanshan had weak fusel flavour and some lemon fruity flavour. Shacheng wine had weak fusel flavour, along with green grass and some fruity flavour of raspberry and violet. Manasi wine had the odour of unpleasant fatty acids and phenol due to its high content of fatty acids and volatile phenol. The sensory analysis confirmed the aroma prediction from the active odorants of the sample wines. Changli wine had the highest sensory scores, while Manasi wine had the worst evaluation of aroma, taste and harmony. The results suggest that the Merlot variety is more suitable for planting in Changli than in the Manasi region.